Deficits in proprioception and strength may contribute to the impaired postural stability among individuals with functional ankle instability - Liu, Yanhao; Dong, Shiyu; Wang, Qi; Liu, Ziyin; Song, Qipeng; Shen, Peixin (Frontiers in Physiology, 2024)
Purpose: The correlations of postural stability with proprioception and strength may explain the recurrent sprains among individuals with functional ankle instability (FAI). This study aimed to compare anterior-posterior (AP) and medial-lateral (ML) postural stability, along with ankle proprioception and strength between individuals with and without FAI and investigated their correlations.Methods: Forty participants with FAI and another 40 without FAI were recruited. Their postural stability, represented by time to stabilization (TTS) in the AP (TTSAP) and ML (TTSML) directions, was calculated by the ground reaction force during jumping onto a force plate. Their ankle proprioception and strength during plantarflexion/dorsiflexion and inversion/eversion were measured using a proprioception device and a strength testing system, separately.Results: Individuals with FAI had longer TTSAP (p=0.015) and TTSML (p=0.006), larger ankle proprioception thresholds (p=0.000-0.001), and less strength (p=0.001-0.017) than those without FAI. Correlations between strength and TTSAP were detected among individuals with (ankle plantarflexion, r=-0.409, p=0.009) and without FAI (ankle plantarflexion, r=-0.348, p=0.028; ankle dorsiflexion, r=-0.473, p=0.002). Correlations of proprioception (ankle inversion, r=0.327, p=0.040; ankle eversion, r=0.354, p=0.025) and strength (ankle eversion, r=-0.479, p=0.002) with TTSML were detected among individuals without FAI but not among those with FAI.Individuals with FAI have worse postural stability and proprioception and less strength. Their proprioception and strength decreased to a point where they could not provide sufficient functional assistance to the ML postural stability. Improvements in proprioception and strength may be keys to prevent recurrent ankle sprains among individuals with FAI.